Research of VC Based Simulation Test System for Automotive ABS - Zhang Wei; Guo Xuexun; Wang Bin (Institute of Advanced Engineering and Science, 2013)
A simulation test and analysis system for ABS control strategy was developed through the joint of VC++6.0 development platform and MATLAB/Simulink simulation platform. And the simulation test for ABS control strategy on four typical roads was carried out. Besides, the test results were analyzed. The test results showed that the system is able to give a good simulation of vehicles and roads and has the capacity of offering a good detection analysis. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1892